On the exponential Diophantine equation a^x+lb^y=c^z

Type: Article

Publication Date: 2016-01-01

Citations: 4

DOI: https://doi.org/10.12988/ija.2016.6747

Locations

  • International Journal of Algebra - View

Similar Works

Action Title Year Authors
+ On the exponential Diophantine equation a x +b y =c z 2011 Nobuhiro Terai
+ On the exponential Diophantine equation a^{2x}+a^xb^y+b^{2y}=c^z 2013 Nobuhiro Terai
Kei Takakuwa
+ On the exponential Diophantine equation a[x]+b[y]=c[z] 2012 隆史 宮崎
+ On the Diophantine equation a^x = b^y + c^z 1976 Toshihiro Hadano
+ PDF Chat On the diophantine equation $x^2 + b^y = c^z$ 1998 Pingzhi Yuan
Wang Jia-bao
+ On the Exponential Diophantine Equation a~(2x)+(3a~2-1)~y=(4a~2-1)~z 2007 Yongzhong Hu
+ PDF Chat A Note on the Exponential Diophantine Equation $a^x+db^y=c^z$ 2001 LE Mao-hua
+ The Exponential Diophantine Equation |a~x-b~y|=c 2009 Bo He
+ A study on the exponential Diophantine equation $a^x+(a+b)^y=b^z$ 2019 Takafumi Miyazaki
Nobuhiro Terai
+ On the exponential Diophantine equation $(a^{n}-1)(b^{n}-1)=x^{2}$ 2016 Katsumasa Ishii
+ On the Diophantine Equation $(na)^x+(nb)^y=(nc)^z$ 2018 Chen Feng-juan
+ PDF Chat On the Diophantine Equation $\bf 1+x+y=z$ 1992 Leo J. Alex
Lorraine L. Foster
+ On the diophantine equation $$la^x + mb^y = nc^z$$ l a x + m b y = n c z 2018 S. Subburam
+ On the diophantine equation $x^x y^y = z^z$ 1990 James A. Ward
+ On the Diophantine equation $${a^{x} + b^{y} = (a + 2)^z}$$ a x + b y = ( a + 2 ) z 2016 Takafumi Miyazaki
Alain Togbé
Pingzhi Yuan
+ On the exponential diophantine equation $$\left( am^{2}+1\right) ^{x}+\left( bm^{2}-1\right) ^{y}=(cm)^{z}$$ a m 2 + 1 x + b m 2 - 1 y = ( c m ) z with $$ c\mid m $$ c ∣ m 2016 Ruiqin Fu
Hai Yang
+ On the Exponential Diophantine Equation $$(a^{n}-2)(b^{n}-2)=x^{2}$$ 2022 Zafer Şi̇ar
Refık Keskin
+ On the exponential Diophantine equation $$(3pm^2-1)^x+(p(p-3)m^2+1)^y=(pm)^z$$ ( 3 p m 2 - 1 ) x + ( p ( p - 3 ) m 2 + 1 ) y = ( p m ) z 2016 Nobuhiro Terai
Takeshi Hibino
+ On the Exponential Diophantine Equation $$(m^2+m+1)^x+m^y=(m+1)^z $$ 2020 Murat Alan
+ On the exponential Diophantine equation $$x^{2}+2^{a}p^{b}=y^{n}$$ x 2 + 2 a p b = y n 2015 Huilin Zhu
LE Mao-hua
Gökhan Soydan
Alain Togbé

Works Cited by This (0)

Action Title Year Authors